Studi Penggunaan Beton Pracetak untuk Pembangunan Saluran Irigasi pada Musim Hujan - Chuing, Andrew Suryadi; Murdapa, Fauzan; Purba, Aleksander (Jurnal Profesi Insinyur Universitas Lampung, 2021)
Indonesia was often referred as an agrarian country, whereas an agrarian country is a country where the majority of its citizens work as farmers. With such large number of farmers and fields which are scattered around the country, agricultural infrastructure become one of the most important aspect in the process of building the country. Every year, Kementrian PUPR are offering projects which connected to agricultural infrastructure, whether it’s the construction of a new irrigation system or a rehabilitation of an old irrigation system. Irrigation system are typically build using concrete with on-site casting method. In irrigation system construction, unlike those in housing/ high rise building, concrete casting cannot be done when it’s raining. Rain could seep into the concrete mix and ruin the concrete quality due to excessive water content. One of the alternatives of this problem is by using precast concrete. Studi Penggunaan Beton Pracetak untuk Pembangunan Saluran Irigasi pada Musim Hujan will compare the effectiveness of using precast concrete method with on-site casting method in irrigation system concrete construction in Monsoon Season. This study will be done using analytical method with 3 case samples, which located in Sumatera Selatan and Lampung province. Analysis shows that on-site casting method in irrigation system concrete construction during Monsoon Season are very ineffective, where the concrete work achievement rate of the Monsoon Season is significantly worse compared to the Dry Season. Whereas, precast concrete method in irrigation system concrete construction during Monsoon Season have the same effectiveness compared to Dry Season.